De Dolores, CO à Lolita, TX : Détours et retours à travers "the crazy quilt of forty-eight states" - Marie Bouchet (Anglophonia)
America structures Nabokov’s most famous novel, Lolita. The novel provides a double mapping process: that of the desired body of the nymphet, and that of the vast country where one finds towns called Dolores and Lolita. In Lolita, the landscape is a projection of the heroine on a huge scale. The country and its metonymic nymphet share characterization devices: conjunction of “reality effects” and metafictional elements, structures based on repetitions and doubles, hybrid combinations. Lolita is a nymphet and a little town, but Lolita is also a colorado of words, a Dolores in Tex(t)as. In an attempt at mapping the protagonists’ journeys, the present paper also identifies two geographical poles of the immense American territory: one is in the North-East, and stages the satisfaction of Humbert’s desire, and the other is in Colorado, where Lolita’s suffering is emphasized, and from where she escapes. It is around those poles that the plot, the perspectives in characterization and the thematic lines of the novel are structured.